Load transfer mechanism of O-cell method for offshore foundation considering nonlinear pile-soil interface response - Rui Jiang; Yuke Wang; Zhengyu Fan; Junjing Zhang; Meiju Jiao (Marine Georesources & Geotechnology, 2026)

Spatiotemporal evolution and obstacle factors of the coupling coordination among green development, eco-environmental security, and social well-being in the Yangtze River Economic Belt, China - Yuke Liu; Chenlu Huang; Miaomiao Yang; Ting Fan; Weidong Huang (Journal of Environmental Management, 2026)

Influence of Different Grouting Methods on the Solidification Uniformity of Marine Silt via SICP Technology - Zhengyu Fan; Yuke Wang; Yang Li; Shuailiang Song; Enyue Ji (Journal of Marine Science and Engineering, 2026)
Marine silt is characterized by a high content of fine particles and low permeability, which often result in uneven urease diffusion, local enrichment, and significant variations in solidification performance during soybean urease-induced calcium carbonate precipitation (SICP) treatment. To address these issues, this study experimentally investigated both the preparation of marine silt mechanical specimens and the injection uniformity of the SICP technique. A cylindrical transparent acrylic mold together with a matching grouting device was developed to enable the observable and standardized preparation of marine silt specimens. On this basis, a series of experiments were conducted, including measurements of urease distribution under single SICP grouting, unconfined compressive strength (UCS) tests of solidified specimens, and quantification of calcium carbonate production. The effects of injection direction, injection volume, and injection rate on solidification uniformity and mechanical strength were systematically examined. The results show that the grouting direction governs the stratification characteristics of urease within the specimens. Increasing the grouting volume significantly enhances the total urease content and improves its distribution uniformity. The UCS of the solidified specimens was found to be closely related to the uniformity of urease distribution. Among the tested methods, the multi-round alternating injection mode from both the top and bottom produced the best overall strength performance. The maximum UCS reached 93.81 kPa at a grouting volume of 150 mL and a grouting rate of 5 mL/min. This study clarifies how injection parameters can be optimized to improve the solidification uniformity of fine-grained marine sediments and provides technical support and parameter references for the standardized preparation of SICP-solidified soil mechanical specimens.

Soil aggregates stability is evidently enhanced by super-binding of the N-terminal disordered tail of glomalin to soil minerals - Minghui Jia; Youchao Wang; Jin He; Shan-Ho Chou; Dehua Luo; Linchuan Fang; Jingtao Hou; Yuke Fan; Wenjun Zhang; Hansong Chen; Dejian Zhou; Yurong Liu; et al. (Soil Biology and Biochemistry, 2025)

Temperature and water availability drive vegetation resilience dynamics in China: An empirical study from causal perspective - Jiapei Wu; Qikang Zhao; Yuke Zhou; Yong Ni; Junfu Fan (Journal of Geographical Sciences, 2025)

Soil organic matter enhances urease-mediated microbially induced carbonate precipitation: Dual benefits for inorganic carbon sequestration and cadmium immobilization - Chonghao Jia; Yuke Fan; Qiangqiang Wei; Lijun Wang; Wenjun Zhang (Journal of Hazardous Materials, 2025)

Treatment of Livestock and Poultry Breeding Wastewater by Multistage Series System: Pollutant Removal Efficiency and Mechanism - Yuke Fan; Wenying Qu; Xiangchun Li; Shenglin Liu; Junfeng Li (Water, Air, & Soil Pollution, 2025)

Experimental study on macro-micro effectiveness of Yellow River silt solidified by using soybean-induced carbonate precipitation (SICP) technology - Yuke Wang; Hao Chen; Yanbo Chen; Meiju Jiao; Zhengyu Fan (Marine Georesources & Geotechnology, 2025)

Competitive adsorption mechanisms of phosphorus species on montmorillonite-iron oxyhydroxide complexes - Chonghao Jia; Jialin Chi; Yuke Fan; Lihong Qin; Tao Ren; Christine V. Putnis; Wenjun Zhang (Chemical Geology, 2025)

Aluminum substitution stabilizes organic matter in ferrihydrite transforming into hematite: A molecular analysis - Yuke Fan; Jialin Chi; Lijun Wang; Chonghao Jia; Wenjun Zhang (Science of The Total Environment, 2024)

Assembly processes and co-occurrence of bacterial communities in tree rhizosphere under Pb-Zn contamination - Hongyang Xu; Ziying Zou; Yuke Jin; Yakov Kuzyakov; Xinhao Huang; Xiaohong Wu; Fan Zhu (Journal of Hazardous Materials, 2024)

Direct observations of nanoscale brushite dissolution by the concentration-dependent adsorption of phosphate or phytate - Xinfei Ge; Yuke Fan; Hang Zhai; Jialin Chi; Christine V. Putnis; Lijun Wang; Wenjun Zhang (Water Research, 2024)

Molecular mechanisms of phosphorus immobilization by nano-clay mediated by dissolved organic matter - Chonghao Jia; Yuke Fan; Jialin Chi; Christine V. Putnis; Chuanqin Huang; Wenjun Zhang (Chemical Geology, 2023)

Association between meteorological factors and varicella incidence: a multicity study in Yunnan Province, China - Hao Wang; Shanjun Huang; Zhaohan Wang; Hua Zhen; Zhuo Li; Wenqi Fan; Menghan Lu; Xin Han; Lanping Du; Meifang Zhao; Yuke Yan; Xinyao Zhang; et al. (Environmental Science and Pollution Research, 2023)

Bioactive components and beneficial bioactivities of flowers, stems, leaves of Lonicera japonica Thunberg: A review - Yuke Li; Long Xie; Kai Liu; Xiaofang Li; Fan Xie (Biochemical Systematics and Ecology, 2023)

Retention of soil organic matter by occlusion within soil minerals - Jialin Chi; Yuke Fan; Lijun Wang; Christine V. Putnis; Wenjun Zhang (Reviews in Environmental Science and Bio/Technology, 2022)

Evaluation of freeze–thaw erosion in Tibet based on the cloud model - Junfu Fan; Taoying Hu; Xiao Yu; Jiahao Chen; Liusheng Han; Yuke Zhou (Frontiers of Earth Science, 2021)

NestNet: a multiscale convolutional neural network for remote sensing image change detection - Xiao Yu; Junfu Fan; Jiahao Chen; Peng Zhang; Yuke Zhou; Liusheng Han (International Journal of Remote Sensing, 2021)

Estimation of Landscape Pattern Changes in BRICS from 1992 to 2013 Using DMSP-OLS NTL Images - Junfu Fan; Huixin He; Taoying Hu; Peng Zhang; Xiao Yu; Yuke Zhou (Journal of the Indian Society of Remote Sensing, 2019)